INTEGRATING KNOWLEDGE MANAGEMENT AND COMMUNICATION STRATEGIES TO ENHANCE CRISIS RESILIENCE: A PRISMA-BASED SYSTEMATIC REVIEW - Siti Nordarma Ab Rahman; Nor Shafrin Ahmad (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
In the face of unprecedented global crises, the importance of effective knowledge management (KM), organisational learning (OL), crisis communication, public health management, and resilience across sectors has become paramount. This systematic review employs the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework to rigorously synthesise findings from 22 key articles out of an initial 157, categorising them into three core themes: Knowledge Management and Organisational Learning in Crisis, Crisis Communication and Public Health Management, and Crisis Impact and Resilience in Various Sectors. The review reveals that effective knowledge-sharing and adaptive learning mechanisms enable organisations to respond adeptly to dynamic crises. Meanwhile, transparent, evidence-based communication strategies are essential for maintaining public trust and effective crisis management. Additionally, it highlights that resilience is multi-dimensional, requiring sector-specific strategies, adaptive capacity, resource availability, and inter-sectoral collaboration to mitigate adverse effects and foster recovery. In conclusion, the synthesis underscores the necessity for integrated approaches encompassing KM, effective communication, and adaptive strategies across different sectors to enhance crisis preparedness and response.